Interaction, emotion and cognition, an integrative approach to the understanding of human behavior - Bächler, Rodolfo Carlos; Poblete, Octavio Gabriel (Anales de Psicología / Annals of Psychology, 2012)
In spite of the reached advances during the past few years, modern psychology doesn’t count today on an integrated conceptual frame that allows to understand in a global way the phenomenon of the human behavior. One of the majors contributions in this sense, was given by the development of the systemic therapy, approach that has allowed to partly overcome the isolated vision of the human conduct, in favor of an interactive and contextual approach of it. Against this background, the notion of interaction rules appears as the key element to the development of intervention tools. Nevertheless, even though the interactional approach (IA) and the systemic therapy (ST) have developed interesting psychological distinctions and useful tools for the therapeutic change, they didn’t have same success when they had to explain theoretically how to arise, maintain and change the interaction rules, questions that, as we will see in this article, depend on the coupling of physical, emotional and mental dimensions of the individual that interact. This proposal aims to integrate these dimensions into a model that allows to develop analysis criteria of the interaction in different contexts, and facilitate the later creation of change devices. In order to fulfill this objective the authors will consider the contributions given by the interactional approach of familiar therapy, humanist psychology and cognitive science, developing a proposal that considers as central axis of its arguments, the explanation of the sprouting of the interaction patterns, as a subject that emerges from the connection of different characteristics from the individual that interact. The model is assumed as a tentative and theoretical speculation of ideas and concepts belonging to different sources of knowledge, therefore the discussion about its relevance as well as its empirical validation, remain as necessary task for the investigators interested in the subject.